KOMPARASI PENGGUNAAN METODE THE POWER OF TWO DAN TALKING STICK TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AL-QUR’AN HADIS - Imam Mashuri; Faza Faizatuz Zain (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
This study aims to determine the effect of using The Power of Two method on student learning outcomes, and to determine the effect of using the Talking Stick method on student learning outcomes, as well as to determine the differences in student learning outcomes using The Power of Two and Talking Stick methods in the subjects of the Qur'an Hadith class VII MTs Negeri 5 Banyuwangi. Based on the observations, information was obtained that teachers delivering learning materials still often use simple and limited learning methods. Teachers more often use the lecture method so that students tend to feel bored and bored because of the very monotonous way of delivering material. This research is a quantitative type research. Data collection techniques use observation, documentation, tests, and interviews. Data analysis techniques include prerequisite tests consisting of normality tests, homogeneity tests, while hypothesis tests use the Paired Sample T Test. The results of the Paired Sample T Test show that the calculated t value of post-learning student learning outcomes with The Power of Two method is -5,405 while for post-learning student learning outcomes with the Talking stick method is -9,477, meaning that the value of student learning outcomes influenced by the Talking Stick method is higher than the learning outcomes of students affected by The Power of Two method (-9,477>-5.405). Based on the calculation of the correlation between the two methods, the Power of Two method is worth 411 and the Talking Stick method is worth 814. Thus it is concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected.